Two Cases of 9p Deletion Syndrome and a Case of Partial Trisomy 8 and Partial Monosomy 9p - Ökten, G.; Sezer, Ö.; Küçüködük, S.; Ogur, G.; Güneş, S. (Medecine et Hygiene, 2009)
Two cases of 9p deletion syndrome and a case of partial trisomy 8 and partial monosomy 9p: We report 3 girls with mental retardation (MR), distinctive malformations of the skull and facial region, including trigonocephaly, small palpebral fissures, and unusually midface hypoplasia, congenital heart defects which are characteristics of monosomy 9p. We performed GTG banding and fluorescence in situ hybridization (FISH) method in all cases. By using cytogenetic methods, three terminal deletions of the short arm of the chromosome 9 were identified and in 2 patients the deletion was de novo, and one patient inherited deletion. FISH analysis showed 46,XX,del(9)(pter→ p22).ish del(9)(pter→p22) in two patients and 46,XX,-9,+der(9)t(8;9)(q24.3;p22)pat. ish der(9)t(8;9)(q24.3;p22)pat (305J7-T7xl,wcp8+,wcp9+) in the third patient. This report compares the symptoms and features of our patients with previously reported patients with a 9p deletion syndrome.
Keywords: 9P Deletion; Fish; High Resolution G-Banding; Translocation